Solid electrolyte film, preparation method thereof and lithium ion battery

By using a combination of base membrane skeleton and high-performance composite electrolyte materials in the solid electrolyte film, a "reinforced concrete" structure is formed, which solves the incompatibility problem between ionic conductivity and mechanical strength of the solid electrolyte film, and achieves efficient synergistic improvement of ionic conductivity and mechanical strength.

CN119695257APending Publication Date: 2025-03-25TIANFU JIANGXI LAB
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411826731.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

Currently, solid electrolyte films have incompatibility between ionic conductivity and mechanical strength, making it difficult to prepare an ideal solid electrolyte material with excellent ionic conductivity and mechanical support properties.

Method used

The base membrane skeleton is used as a support, and through the modification of the base membrane and the design of the pore structure, the high-performance composite solid electrolyte material is uniformly filled to form a thin film with a "reinforced concrete" structure, achieving decoupling and regulation of ionic conductivity and structural stability.

Benefits of technology

By constructing the "reinforced concrete" structure, the coordinated improvement of the high ionic conductivity and mechanical strength of the solid electrolyte film is achieved, and the technical difficulties in the prior art are overcome.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695257A_ABST
    Figure CN119695257A_ABST
Patent Text Reader

Abstract

The invention discloses a solid electrolyte thin film and a preparation method thereof, and a lithium ion battery, the solid electrolyte thin film comprises a base film and a solid electrolyte material, a base film skeleton is used as a support, the solid electrolyte material is uniformly filled or permeated in pores of the base film, and a thin film with a reinforced concrete type structure is formed; the surface of the base membrane is modified by a functional reagent containing sulfonic groups or carboxyl groups; the thickness of the base membrane is 3-50 microns, and the porosity of the base membrane is 5-70%. According to the invention, the adjustable mechanical support capability (reinforcing steel bar) is provided for the electrolyte by using the base membrane framework, meanwhile, the high-performance composite solid electrolyte material (concrete) is uniformly filled in the base membrane pores to enhance the ionic conductivity, and the decoupling regulation and control of the ionic conductivity and the structural stability of the solid electrolyte film are realized by constructing the reinforced concrete structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a solid electrolyte film and a preparation method thereof, and a lithium ion battery. Background Art

[0002] Solid electrolytes, as the core components of solid-state batteries, can be divided into three categories according to their composition: inorganic, polymer and composite solid electrolytes.

[0003] Oxide inorganic solid electrolytes use oxygen ions or lithium ions as carriers and have excellent thermal stability and mechanical strength, but their ionic conductivity is lower than that of liquid electrolytes. Oxide solid electrolyte films are generally prepared by sputtering deposition, chemical vapor deposition and sintering, which have problems such as high-temperature preparation leading to complex processes, high brittleness of the film, difficulty in adapting to the mechanical strain of the battery structure, and high interface impedance.

[0004] Sulfide inorganic solid electrolytes have high ionic conductivity, comparable to liquid electrolytes, and have good interface compatibility. Thin films are generally prepared by mechanical ball milling, hot pressing sintering, and solution casting. However, sulfides have poor stability, are sensitive to moisture, and are easily decomposed to produce hydrogen sulfide. Therefore, strict requirements are placed on the preparation environment and the production cost is high.

[0005] Polymer solid electrolytes have excellent flexibility and good processability, but low room temperature ionic conductivity, and need to be improved by doping with salts and nanofillers. Polymer solid electrolyte films are generally prepared by solution casting, hot pressing and electrospinning. In addition, polymer solid electrolytes also have problems such as a narrow electrochemical stability window, insufficient thermal / chemical stability, and difficulty in balancing conductivity improvement and mechanical properties.

[0006] Composite solid electrolytes combine the advantages of inorganic materials and polymers, and are both flexible and highly conductive. Methods such as blending, in-situ polymerization, and layer-by-layer assembly are mainly used to prepare composite solid electrolyte films. However, the composite solid electrolyte system is complex, the uniform distribution of components is difficult to control, the inorganic-polymer interface has poor compatibility, which affects the ion transfer efficiency, and it is difficult to directly form a self-supporting and stable membrane structure.

[0007] In summary, there is still incompatibility between ionic conductivity and mechanical strength in current solid-state electrolyte films, making it difficult to prepare ideal solid-state electrolyte materials that have both excellent ionic conductivity and mechanical support properties.

[0008] In view of this, this patent application is filed. Summary of the invention

[0009] In order to solve the above technical problems, the present invention provides a solid electrolyte film and a preparation method thereof, and also uses the solid electrolyte film as a raw material to obtain a lithium ion battery.

[0010] The present invention is achieved through the following technical solutions:

[0011] The first object of the present invention is to provide a solid electrolyte film, comprising a base film and a solid electrolyte material, with the base film skeleton as support, and the solid electrolyte material is uniformly filled or infiltrated in the pores of the base film to form a film with a "reinforced concrete" structure;

[0012] The surface of the base film is modified by a functionalizing agent containing a sulfonic acid group or a carboxyl group;

[0013] The thickness of the base film is 3-50 μm, and the porosity of the base film is 5%-70%.

[0014] The present invention innovatively proposes a solid electrolyte membrane with a "reinforced concrete" structure, which aims to utilize the base membrane skeleton to provide adjustable mechanical support capacity ("reinforcement") for the electrolyte, while uniformly filling the base membrane pores with high-performance composite solid electrolyte materials ("concrete") to enhance ionic conductivity, and realize decoupling regulation of the ionic conductivity and structural stability of the solid electrolyte membrane by constructing a "reinforced concrete" structure.

[0015] At the same time, the inventors considered that there would be difficulties when using the basement membrane as the overall framework structure of the electrolyte film, because the ionic conductivity of the basement membrane itself is general and cannot be directly used as an electrolyte, which is the first technical difficulty; and when the basement membrane is used as the main structure, the penetration and uniform film formation of the electrolyte become the key. If the penetration and uniform film formation of the electrolyte cannot be overcome, the ionic conductivity performance of the film will be poor, which is the second technical difficulty. The inventors modified the surface of the basement membrane, using polymers / small molecules containing sulfonic acid groups (-SO3H) or carboxyl groups (-COOH) to adhere to the surface of the basement membrane, and improve the affinity of the basement membrane with the solid electrolyte, which is conducive to the synergistic improvement of mechanical strength and ionic conductivity. At the same time, the pore structure and porosity of the basement membrane are reasonably designed, thereby achieving complete filling and penetration of the electrolyte precursor (i.e., solid electrolyte material) in the gap, forming a continuous solid electrolyte phase, and ensuring the high ionic conductivity of the solid electrolyte supported by the basement membrane.

[0016] As a preferred design, the base membrane is any one of polyethylene film (PE), polypropylene film (PP), glass fiber reinforced polypropylene film, nylon film (PA), polyvinylidene fluoride film (PVDF), PVDF-CTFE fiber membrane, polyvinyl nitrile film (PAN), and glass fiber membrane.

[0017] In the present invention, by adjusting the parameters such as the base membrane material, thickness, porosity, etc., the mechanical support characteristics of the base membrane are optimized, and the filling or penetration of the solid electrolyte precursor in the pores of the base membrane is regulated, in order to form a continuous solid electrolyte phase and achieve decoupled regulation of the ionic conductivity and structural stability of the solid electrolyte film.

[0018] As a preferred design, the functionalizing agent containing a sulfonic acid group is any one of sodium sulfate and sodium p-toluenesulfonate or a mixture of the two, and the functionalizing agent containing a carboxyl group is acrylic acid.

[0019] As a preferred design, the raw materials of the solid electrolyte material include lithium salt, polymer, and super ion conductor additive;

[0020] The lithium salt is any one of LiCl, LiBr, Li2S, LiFSI, LiPF6, and LiNO3, or a mixture of several thereof;

[0021] The polymer is any one of polyvinylidene fluoride, polyethylene oxide, polymethyl methacrylate, polytetrafluoroethylene, or a mixture of two or more thereof;

[0022] The superionic conductor additive is a two-dimensional structural material.

[0023] The void filling formula of the solid electrolyte provided by the present invention is more suitable for the framework with the base film as the overall structure, so as to achieve complete filling and penetration of the electrolyte precursor in the void, form a continuous solid electrolyte phase, and ensure the high ion conductivity of the solid electrolyte supported by the base film. The superions in the formula can increase the lithium ion transmission channels and sites, improve the intrinsic ion conductivity of the material, and realize the regulation of the conductivity of the solid electrolyte.

[0024] As a preferred design, the two-dimensional structural material is any one of graphene, graphene derivatives, boron nitride, carbon nitride, two-dimensional layered halides, transition metal sulfides, two-dimensional transition metal carbides, and two-dimensional transition metal nitrides, or a mixture of two or more thereof.

[0025] The second object of the present invention is to provide a method for preparing any of the above solid electrolyte films, comprising the following steps:

[0026] The surface of the base film is modified by a functionalizing agent under the action of a modifier;

[0027] Preparation of solid electrolyte materials: adding lithium salt, polymer, and superionic conductor additives into a mixed solvent, crushing and stirring;

[0028] Coating and filling of solid electrolyte materials and solidification of solid electrolyte.

[0029] As a preferred design, the modifier is any one of polyvinyl alcohol, polyacrylonitrile, chitosan or a mixture of several thereof;

[0030] The mass concentration of the modifier is 1-10%, and the mass concentration of the functionalizing agent is 0.1-10%.

[0031] As a preferred design, the modification process is:

[0032] (1) Cleaning the base film: the base film can be ultrasonically cleaned with ethanol and deionized water for 5 to 20 minutes each to remove surface impurities and oil stains;

[0033] (2) immersing the base film in a dispersion solution containing a functionalizing agent, ensuring that the solution completely soaks the base film, and dipping for 5 to 30 minutes, with the temperature controlled at 20 to 50° C.; water or an organic solvent is the dispersion solution, and the organic solvent is a mixture of one or more of ethanol and dimethylformamide (DMF);

[0034] (3) Remove the base film, remove excess solvent, and dry at 50 to 80° C. for 20 to 100 minutes.

[0035] As a preferred design, during the preparation of the solid electrolyte material, the molar concentration of the lithium salt is 0.4-0.7 mol / L, the mass concentration of the polymer is 80-130 g / L, and the mass concentration of the superionic conductor additive is 2.4-26 g / L;

[0036] Adding lithium salt, polymer and superionic conductor additive into the mixed solution, crushing, stirring and mixing evenly to achieve uniform preparation of precursor slurry;

[0037] The mixed solution is one or two of dimethylformamide (DMF), N-methylpyrrolidone (NMP), and tetrahydrofuran (THF);

[0038] and / or, the coating speed during coating and filling is 10-100 mm / s;

[0039] And / or, when the solid electrolyte is solidified, it is first dried at room temperature for 6 to 24 hours, and then dried at 80 to 100° C. for 0.5 to 5 hours.

[0040] As a preferred design, a directional electric field is applied to the solid electrolyte film during the room temperature drying process to form a directional arranged two-dimensional conductive channel;

[0041] Preferably, the direction of the applied electric field is 90°, the voltage is 100 V, and the time is 2 h.

[0042] The present invention makes full use of the conductive channel characteristics of the two-dimensional structural material and applies a directional electric field to the solid electrolyte film during the room temperature drying process to form a directional arranged two-dimensional conductive channel to further improve the conductive performance.

[0043] The third object of the present invention is to provide a lithium ion battery using the solid electrolyte film as described in any one of the above items as a raw material.

[0044] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0045] 1. The solid electrolyte film provided in the embodiment of the present invention utilizes the base membrane skeleton to provide adjustable mechanical support capacity ("rebar") for the electrolyte, and at the same time uniformly fills the base membrane pores with high-performance composite solid electrolyte materials ("concrete") to enhance ionic conductivity. By constructing a "reinforced concrete" structure, the decoupling regulation of the ionic conductivity and structural stability of the solid electrolyte film is achieved, which provides a new method for the design and preparation of solid electrolyte films for application in different practical scenarios.

[0046] 2. The present invention overcomes the technical difficulty that the prior art cannot take into account both mechanical support capacity and ionic conductivity, and optimizes the mechanical properties of the "rebar" and the filling of the solid electrolyte by means of material selection, thickness and porosity control of the base membrane; by optimizing lithium salts and superionic conductor additives to construct "concrete" with high ionic conductivity, and modifying the surface of the base membrane, the affinity between the electrolyte and the base membrane is synergistically improved, thereby achieving complete filling and penetration of the electrolyte precursor in the gap, forming a continuous solid electrolyte phase, ensuring the high ionic conductivity of the solid electrolyte supported by the base membrane, and synergistically improving the mechanical strength and ionic conductivity performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:

[0048] Figure 1 It is a schematic diagram of a solid electrolyte film structure provided by the present invention.

[0049] Figure 2 This is the flow chart for the preparation of solid electrolyte film with "reinforced concrete" structure. DETAILED DESCRIPTION

[0050] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0051] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0052] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0053] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0054] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0055] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0056] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0057] Embodiment 1:

[0058] Step 1: Selection of materials and structural parameters of the base film. The base film material is polyethylene PE, the base film thickness is 9 μm, and the porosity is 50%.

[0059] Step 2: Surface modification of the base film. Use water as solvent to prepare a modification solution, which contains a modifier and a functionalizing agent. The modifier is polyvinyl alcohol (PVA) with a mass concentration of 2%, and the functionalizing agent of the carboxyl group (-COOH) is acrylic acid with a mass concentration of 1%. First, use ethanol and deionized water to ultrasonically clean the base film for 10 minutes each to remove surface impurities and oil stains; the cleaned base film is dipped in the modification solution for 10 minutes, and ensure that the solution completely infiltrates the base film, and the temperature is controlled at 30°C; after the treatment, remove the base film, remove excess solvent, and dry it at 60°C for 60 minutes.

[0060] Step 3: Preparation of solid electrolyte precursor. The lithium salts are LiCl, LiFSI and LiNO3, with a total concentration of 0.6 mol / L and a molar concentration ratio of 1:1:1; the polymers are polyvinylidene fluoride PVDF and polyethylene oxide PEO, with a total concentration of 110 g / L and a mass ratio of 1:1; the ion conductor additive is a graphene derivative with a concentration of 10 g / L; the solvent is DMF and N-methylpyrrolidone NMP, with a volume ratio of 1:3. The precursor slurry is uniformly prepared by means of crushing and stirring.

[0061] Step 4: coating and filling of solid electrolyte: The solid electrolyte slurry is coated and filled by scraping with a doctor blade at a coating speed of 50 mm / s.

[0062] Step 5: Solidification of solid electrolyte. The solid electrolyte solidification takes 12 hours at room temperature and 2 hours at 90°C.

[0063] Step 6: Mechanical and electrical performance testing.

[0064] Ion conductivity test: Cut the solid electrolyte membrane into discs, test the thickness, and then sandwich it between two pieces of stainless steel to form a "sandwich" structure. Place it in a button battery housing and inject a liquid electrolyte of DC:DMC:DEC=1:1:1 / LiPF6 to encapsulate a button secondary battery. Test the ionic conductivity of the button secondary battery using an electrochemical workstation at 25°C, and set the test frequency to 10 -1 ~10 5 Hz, with an amplitude of 10mV.

[0065] Tensile strength test: Cut a 15mm wide specimen, the initial distance between the clamps is 100mm, and the test speed is 250mm / min.

[0066] Puncture strength test: Cut 5 specimens with a diameter of 100 mm, with uniform thickness, without wrinkles, folds, stains and other defects, and puncture them at a speed of 50 mm / min. The arithmetic average of the puncture force of the 5 samples is taken as the final test result of the puncture strength.

[0067] Example 2: Compared with Example 1, the base film supporting material is changed to polypropylene PP.

[0068] Example 3: Compared with Example 1, the base membrane support material is changed to glass fiber reinforced PP.

[0069] Example 4: Compared with Example 1, the base film support material is changed to nylon PA.

[0070] Example 5: Compared with Example 1, the base membrane support material is changed to PVDF-CTFE fiber.

[0071] Example 6: Compared with Example 1, the base membrane supporting material is changed to glass fiber.

[0072] Example 7: Compared with Example 1, the base film support material is changed to polyvinylidene fluoride PVDF.

[0073] Example 8: Compared with Example 1, the base film support material is changed to polyvinyl nitrile PAN.

[0074] Example 9: Compared with Example 1, the thickness of the base film is changed to 3 μm.

[0075] Example 10: Compared with Example 1, the thickness of the base film is changed to 20 μm.

[0076] Example 11: Compared with Example 1, the porosity of the base film is changed to 30%.

[0077] Example 12: Compared with Example 1, the porosity of the base film is changed to 60%.

[0078] Example 13: Compared with Example 1, when the solid electrolyte is solidified, a directional electric field is applied to the solid electrolyte film during the room temperature drying process, the electric field direction is 90°, the voltage is 100V, and the time is 2h.

[0079] Example 14: Compared with Example 1, the two-dimensional structural material is changed to carbon nitride.

[0080] Example 15: Compared with Example 1, the two-dimensional structural material is changed to a mixture of carbon nitride and graphene derivatives, with a total mass concentration of 10 g / L and a mass concentration ratio of 1:1.

[0081] Comparative Example 1: Compared with Example 1, the base film support material is not used, and the mixed solid electrolyte material is directly prepared. Comparative Example 2: Compared with Example 1, the base film is not modified.

[0082] Comparative Example 3: Compared with Comparative Example 1, the thickness of the base film is changed to 2 μm.

[0083] Comparative Example 4: Compared with Comparative Example 1, the thickness of the base film is changed to 65 μm.

[0084] Comparative Example 5: Compared with Comparative Example 1, the porosity of the base film is changed to 3%.

[0085] Comparative Example 6: Compared with Comparative Example 1, the porosity of the base film is changed to 78%.

[0086] The specific test results are shown in Table 1.

[0087] Table 1 Mechanical and electrical properties test results

[0088]

[0089] As can be seen from Table 1, the puncture strength and tensile strength of the solid electrolyte film obtained in each embodiment of the present invention are at a relatively high level, with the maximum puncture strength reaching 650gf, the maximum tensile strength reaching 200Mpa, and the maximum ionic conductivity being about 1.1mS / cm. By comparing Example 13 with Example 1, it can be seen that when a directional electric field is applied to the film during the curing stage, the ionic conductivity of the film is improved.

[0090] Comparing Example 1 with Comparative Example 1, when the basement membrane is not used as the supporting material, the mechanical properties are significantly reduced, and the conductivity is also lower than that of Example 1. It can be seen that the mechanical strength of the film will also significantly affect its ionic conductivity. Comparing Example 1 with Comparative Example 2, when the basement membrane is not modified, the puncture strength and tensile strength of Comparative Example 2 are equivalent to those of Example 1, but the ionic conductivity is significantly lower than that of Example 1, indicating that when the basement membrane is used as the supporting material, the strength of the film is acceptable, but the ionic conductivity is obviously insufficient.

[0091] From the comparison between comparative examples 3 and 4 and embodiment 1, it can be seen that when the thickness of the base film is less than 3 μm or greater than 50 μm, the strength and ionic conductivity of the film are worse than those of embodiment 1. From the comparison between comparative examples 5 and 6 and embodiment 1, it can be seen that when the porosity of the base film is less than 5% or greater than 70%, either the strength is acceptable but the conductivity is low, or the conductivity is high but the strength is obviously very low. In summary, it can be seen from each comparative example that the comparative examples cannot take into account both the mechanical properties and electrical properties of the film, and cannot obtain a film with good comprehensive performance.

[0092] The above specific implementation methods further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above are only specific implementation methods of the present invention and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A solid electrolyte film, characterized in that: It includes a base membrane and a solid electrolyte material, with the base membrane skeleton as support, and the solid electrolyte material is evenly filled or infiltrated in the pores of the base membrane to form a film with a reinforced concrete structure; The surface of the base film is modified by a functionalizing agent containing a sulfonic acid group or a carboxyl group; The thickness of the base film is 3-50 μm, and the porosity of the base film is 5%-70%.

2. A solid electrolyte film according to claim 1, characterized in that: The base film It is any one of polyethylene film, polypropylene film, glass fiber reinforced polypropylene film, nylon film, polyvinylidene fluoride film, PVDF-CTFE fiber membrane, polyvinyl nitrile film, and glass fiber membrane.

3. A solid electrolyte film according to claim 2, characterized in that: The functionalizing agent containing sulfonic acid group is any one of sodium sulfate and sodium p-toluenesulfonate or a mixture of the two, and the functionalizing agent containing carboxyl group is acrylic acid.

4. A solid electrolyte film according to any one of claims 1 to 3, characterized in that: The raw materials of the solid electrolyte material include lithium salt, polymer, and super ion conductor additive; The lithium salt is any one of LiCl, LiBr, Li2S, LiFSI, LiPF6, and LiNO3, or a mixture of several thereof; The polymer is any one of polyvinylidene fluoride, polyethylene oxide, polymethyl methacrylate, polytetrafluoroethylene, or a mixture of two or more thereof; The superionic conductor additive is a two-dimensional structural material.

5. A solid electrolyte film according to claim 4, characterized in that: The two-dimensional structural material is any one of graphene, graphene derivatives, boron nitride, carbon nitride, two-dimensional layered halides, transition metal sulfides, two-dimensional transition metal carbides, and two-dimensional transition metal nitrides, or a mixture of two or more thereof.

6. A method for preparing a solid electrolyte film according to any one of claims 1 to 5, characterized in that: The following steps are involved: The surface of the base film is modified by a functionalizing agent under the action of a modifier; Preparation of solid electrolyte materials: adding lithium salt, polymer, and superionic conductor additives into a mixed solvent, crushing and stirring; Coating and filling of solid electrolyte materials and solidification of solid electrolyte.

7. The method for preparing a solid electrolyte film according to claim 6, characterized in that: The modifier is any one of polyvinyl alcohol, polyacrylonitrile and chitosan or a mixture of several thereof; The mass concentration of the modifier is 1-10%, and the mass concentration of the functionalizing agent is 0.1-10%.

8. The method for preparing a solid electrolyte film according to claim 6, characterized in that: The modification process is: (1) Cleaning the basement membrane; (2) immersing the base film in a dispersion solution containing a functionalizing agent, ensuring that the solution completely soaks the base film, and immersing for 5 to 30 minutes at a temperature of 20 to 50° C.; (3) Remove the base film, remove excess solvent, and dry at 50 to 80° C. for 20 to 100 minutes.

9. The method for preparing a solid electrolyte film according to claim 6, characterized in that: In the preparation process of the solid electrolyte material, the molar concentration of the lithium salt is 0.4-0.7 mol / L, the mass concentration of the polymer is 80-130 g / L, and the mass concentration of the superionic conductor additive is 2.4-26 g / L; Adding lithium salt, polymer and superionic conductor additive into the mixed solution, crushing, stirring and mixing the mixture evenly; The mixed solution is one or two of dimethylformamide (DMF), N-methylpyrrolidone (NMP), and tetrahydrofuran (THF); and / or, the coating speed during coating and filling is 10-100 mm / s; And / or, when the solid electrolyte is solidified, it is first dried at room temperature for 6 to 24 hours, and then dried at 80 to 100° C. for 0.5 to 5 hours.

10. The method for preparing a solid electrolyte film according to claim 9, characterized in that: Applying a directional electric field to the solid electrolyte film during the drying process at room temperature to form a directional arranged two-dimensional conductive channel; Preferably, the direction of the applied electric field is 90°, the voltage is 100 V, and the time is 2 h.

11. A lithium ion battery, characterized in that: A solid electrolyte film prepared by the method according to any one of claims 1 to 5 or any one of claims 6 to 10 is used as a raw material.

Citation Information

Cited By

  • Nonwoven fabric for solid electrolyte support layer, and method of manufacturing and use thereof

    CN120465190B

  • Solid film electrolyte chip structure, preparation method, test method and test system

    CN121453884A

  • A solid-state thin-film electrolyte chip structure, a preparation method, a test method and a test system

    CN121453884B